Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 2 - Section 2.3 - The Algebra of Functions - Exercise Set - Page 133: 42



Work Step by Step

$(fg)(x)=f(x)g(x)$ $(fg)(6)=f(6)g(6)$. First, find $f(6)$ and $g(6)$. $f(6)=6^{2}+4\times6=36+24=60$ $g(6)=2-6=-4$ Then, multiply them. $(fg)(6)=f(6)g(6)=60\times(-4)=-240$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.